Acceptance of Learning Styles and the Use of Technology among Students in Mathematics Learning - Shafira, Diva; Maarif, Samsul (IndoMath: Indonesia Mathematics Education, 2025)
This quantitative study examined the relationship between students' learning styles and technology use in math learning. Although digital tools are increasingly integrated into schools, many still overlook students diverse learning styles and their interaction with technology. Prior research often addresses learning styles or technology acceptance separately, with few examining both together, especially in secondary education. This study used a one-time survey involving 1.029 Indonesian students from middle schools, high schools, and vocational schools. Learning styles (visual, auditory, kinesthetic) were measured using a Likert-scale questionnaire. Technology acceptance was assessed through performance expectations, attitudes, perceived usefulness, and e-learning suitability. Data were analyzed using SmartPLS. Results show that attitudes toward technology significantly affect perceived ease of use, e-learning suitability, and performance expectations. These factors influence learning preferences both directly and indirectly. The findings support the technology acceptance model and show its relevance in improving digital-based math learning across Indonesia’s secondary education context.